Universal Geometric Structures: Fractal Symmetries in Ocular Anatomy, Botanical Forms, and Cosmic Networks - Devi, Anitha (Journal of Educational Research and Policies, 2026)
In this study, I propose and validate a geometric and vectorial model of structural analogy across three natural scales: the human eye (retina and iris), the orange (a mesostructural organic system), and the cosmic web (the large - scale structure of the universe). My model, named the Harmonic Octagonal Mesh, is based on radial symmetry, angular subdivision, and spectral response patterns consistently observed in these systems. Through morphometric analysis, spectral comparison, and mathematical vector modeling, I demonstrate that all three structures exhibit central coordination, vectorial convergence, and harmonic organization based on octagonal segmentation. My results support the idea that nature appears to follow a unifying pattern of spatial efficiency and resonance across different scales. This work presents a foundational theoretical and mathematical basis for formulating a new structural postulate and opens perspectives for interdisciplinary research in optics, cosmology, biogeometry, and computational modeling.